Harmonic Mind Maps (MMA) as a metacognitive strategy for reading comprehension in university students - Novoa Castillo, Pedro Félix (2020)
This research aimed to determine the influence of Harmonic Mind Maps (HMM) as a metacognitive strategy in reading comprehension in university students. For this, 310 undergraduate students from the Faculty of Education of the National University of San Marcos (UNMSM in spanish) were worked during the 2nd semester of 2019. The methodology was framed within the quantitative approach and the deductive hypothetical method was followed. Therefore, its design was quasi-experimental. The information was collected through the 2015 CLUni Test. The results showed that the use of MMA as a metacognitive strategy has a positive and significant impact on improving the reading comprehension of university students.